Alzheimer disease: Non-pharmacological and pharmacological management of cognition and neuropsychiatric symptoms. (August 2018) - Loi, Samantha M; Eratne, Dhamidhu; Kelso, Wendy; Velakoulis, Dennis; Looi, Jeffrey CL
Objectives: This clinical update review focuses on the management of cognition and the neuropsychiatric features of Alzheimer's disease (AD) and highlights current issues regarding pharmacological and non-pharmacological treatment, putative therapeutics and recent relevant research findings in this area. Conclusions: AD is a neurodegenerative progressive condition characterised by cognitive impairment and functional decline. Most people with AD will demonstrate neuropsychiatric features, better known as behavioural and psychological symptoms of dementia (BPSD). Early recognition and treatment of BPSD are essential, as these cause considerable distress and carer burden. While there are many disease-modifying therapies for the cognitive symptoms still in the research stage, only symptomatic treatments are currently available for these and the BPSD.